The Role of Ratu Kalinyamat in Past Maritime Successes: As a Study of Archipelago Sea Defense - Anis Nur Laily; Lukman Yudho Prakoso; Puja Sari Putri (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The Kingdom of Demak was the ﬁrst Islamic kingdom on the island of Java, centered in Jepara. The Kingdom of Demak was founded by Raden Patah in the early 16th century and reached its peak of glory under Sultan Trenggono. Jepara is a port city. The name of Queen Kalinyamat appears in the history of the Kingdom of Demak as a female hero who contributed to advancing trade and the navy on the island of Java. The research method in this article uses the historical method, which is the basic principle used in collecting data or sources, critiquing, interpreting, and presenting information or sources in a synthetical way in the form of a historical narrative. The historical method is studied in four steps to obtain complete results, namely heuristics, veriﬁcation, interpretation and historiography. The research phase was carried out by collecting library sources, both primary and secondary. Jepara played an important role for the Kingdom of Demak not only as a trading port, but also as a Demak naval base. The strength of the Demak ﬂeet is centered in Jepara. Queen Kalinyamat's courage in formulating her power strategy made Jepara the maritime axis of Java in the 16th century. Stories of past victories can encourage awareness about maritime history and are expected to be able to answer current problems. Maritime life is a very vital aspect in the history of the Indonesian nation since the 16th century. Jepara's maritime glory during the time of Queen Kalinyamat was supported by a large and strong navy. It is hoped that the story of Queen Kalinyamat can increase a sense of nationalism and increase public awareness that the Indonesian nation has always used the sea and used the sea as part of its life.